Why a System Awarded as “MIE ’99 Best Paper” Failed to Be Used and Hence to Affect Patient’s Health? - Mazzoleni, M. C. (Methods of Information in Medicine, 2006)
Objective: The failure of a promising system is described with the aim of identifying the errors and the unfavourable conditions that led to such a result.Methods: The system, based on the AHCPR guideline for pressure ulcers prevention and integrated into the already existing clinical information system, is aimed at supporting nurse’s activities for: the risk assessment of the inpatient at the beginning of the hospitalization; the prevention plan, customized to each specific patient; the work plan for each day for all the patients; the report of the non-compliances to the GL and of the workload of the nurses.Results: The system was abandoned after a short period. The reported reasons for the abandonment were: too strict constraints in the work-plan and the mandatory updating of the tasks at the end of each shift (both executed and not); the double writing activity, on paper first and afterward on the workstation.The first complaint was almost unrecoverable and not related to the system from the implementation point of view. Portable notebooks and wireless connections to the LAN could have been a solution for the second problem. Simultaneously a portable device at the bed side could have benefited many other features of the clinical information system. We proposed to quantify the added value, if any, due to making the information system available as close as possible to the points on the wards where information are both generated and used. The proposal was rejected.Conclusions: In our experience in a hospital setting, closing the gap among the medical informatics minority, the health professionals and the hospital management, through their collaborative responsibilities and participation in the decision-making process, can make the difference between the success and the failure of a good computer-based solution.
Keywords: Applied medical informatics; success factors; guidelines; evaluation; political factors